Exposure to Perchlorate in Lactating Women and Its Associations With Newborn Thyroid Stimulating Hormone - Ucal, Yasemin; Sahin, Ozlem N.; Serdar, Muhittin; Blount, Ben; Kumru, Pinar; Muhcu, Murat; Eroglu, Mustafa; Akin-Levi, Cansu; Keles, Z. Zeynep Yildirim; Turam, Cem; Valentin-Blasini, Liza; Morel-Espinosa, Maria; et al. (Frontiers in Endocrinology, 2018)
Background: Perchlorate, thiocyanate, and nitrate can block iodide transport at the sodium iodide symporter (NIS) and this can subsequently lead to decreased thyroid hormone production and hypothyroidism. NIS inhibitor exposure has been shown to reduce iodide uptake and thyroid hormone levels; therefore we hypothesized that maternal NIS inhibitor exposure will influence both maternal and newborn thyroid function. Methods: Spot urine samples were collected from 185 lactating mothers and evaluated for perchlorate, thiocyanate, and nitrate concentrations. Blood and colostrum samples were collected from the same participants in the first 48 hours after delivery. Thyroid hormones and thyroid-related antibodies (TSH, fT3, fT4, anti-TPO, anti-Tg) were analyzed in maternal blood and perchlorate was analyzed in colostrum. Also, spot blood samples were collected from newborns (n=185) between 48-72 postpartum hours for TSH measurement. Correlation analysis was performed to assess the effect of NIS inhibitors on thyroid hormone levels of lactating mothers and their newborns in their first 48 postpartum hours. Results: The median of maternal urinary perchlorate (4.00 μg/g creatinine), maternal urinary thiocyanate (403 μg/g creatinine) and maternal urinary nitrate (49117 μg/g creatinine) were determined. Higher concentrations of all three urinary NIS inhibitors (μg/g creatinine) at their 75th percentile levels were significantly correlated with newborn TSH (r= 0.21, p<0.001). Median colostrum perchlorate level concentration of all 185 participants was 2.30 μg/L. Colostrum perchlorate was not significantly correlated with newborn TSH (p>0.05);  however, there was a significant correlation between colostrum perchlorate level and maternal TSH (r=0.21, p<0.01).  Similarly, there was a significant positive association between colostrum perchlorate and maternal urinary creatinine adjusted perchlorate (r=0.32, p<0.001). Conclusion: NIS inhibitors are ubiquitous in lactating women in Turkey and are associated with increased TSH levels in newborns, thus signifying for the first time that co-exposure to maternal NIS inhibitors can have a negative effect on the newborn thyroid function.